2009
DOI: 10.3109/08923970903201748
|View full text |Cite
|
Sign up to set email alerts
|

In vitroimmunomodulatory effects of fractions obtained from aqueous extracts ofLarrea divaricataCav (Jarilla) on mouse peritoneal macrophages

Abstract: These results indicate that NDGA was not the compound responsible for the immunomodulatory action exerted by the aqueous extract from L. divaricata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…We also demonstrated that L. divaricata decoction has immunomodulatory activity both in vitro and in vivo 7,8 . Moreover, fractions isolated from the decoction induced the activation of the innate immune system in vitro 9 . On the other hand, Davicino et al.…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…We also demonstrated that L. divaricata decoction has immunomodulatory activity both in vitro and in vivo 7,8 . Moreover, fractions isolated from the decoction induced the activation of the innate immune system in vitro 9 . On the other hand, Davicino et al.…”
Section: Introductionmentioning
confidence: 50%
“…Fractions were prepared as described previously 9 . Briefly, 7 g of lyophilised material was resuspended in chloroform and chromatographed in a column of silica gel (130 gr) using different chloroform/methanol ratios (97.5 : 2.5; 95 : 5; 92.5 : 7.5; 90 : 10; 80 : 20 and pure methanol) as the mobile phase as described.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations